2021
DOI: 10.1158/1078-0432.ccr-20-4576
|View full text |Cite
|
Sign up to set email alerts
|

A Bispecific Single-Domain Antibody Boosts Autologous Vγ9Vδ2-T Cell Responses Toward CD1d in Chronic Lymphocytic Leukemia

Abstract: Purpose: Although considerable progress has been made with autologous T cell-based therapy in B-cell malignancies, application in chronic lymphocytic leukemia (CLL) lags behind due to disappointing response rates as well as substantial toxicity that is of particular concern in the elderly CLL population. Vg9Vd2-T cells form a conserved T-cell subset with strong intrinsic immunotherapeutic potential, largely because of their capacity to be triggered by phosphoantigens that can be overproduced by CLL and other m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Given this, the potential engagement of therapeutic Abs with the product of Vg9Vd2 cells can provide an efficient alternative against LCs (223). Several studies have shown that gd T cells mediate leukemic regression via a CD16dependent pathway (136,(223)(224)(225)(226), in particular the Vg9Vd2 subtype, which positively regulates CD16 and TNF expression when stimulated with pAgs (227).…”
Section: Antibodies Direct Gd T Cells Against Lcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this, the potential engagement of therapeutic Abs with the product of Vg9Vd2 cells can provide an efficient alternative against LCs (223). Several studies have shown that gd T cells mediate leukemic regression via a CD16dependent pathway (136,(223)(224)(225)(226), in particular the Vg9Vd2 subtype, which positively regulates CD16 and TNF expression when stimulated with pAgs (227).…”
Section: Antibodies Direct Gd T Cells Against Lcsmentioning
confidence: 99%
“…Finally, it has been shown that CD1d is also an attractive target. A recent study showed that CD1d specific single domain Abs can guide γδ T cells ( 226 ). These engagers were able to mobilize and activate these lymphocytes against autologous LCs from patients with CLL.…”
Section: Harnessing γδ T Cells Against Leukemia: From Marrow To Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Vγ9Vδ2-T cells have become a novel potential immunotherapeutic for Chronic Lymphocytic Leukemia (CLL) due to their capacity to be triggered by phosphoantigens which are overproduced by CLL. A nanobody-based CD1d-specific Vγ9Vδ2-T cell engager was generated to induce robust activation and degranulation of Vg9Vd2-T cells and consequent lysis of autologous leukemic cells ( 29 ).…”
Section: Nanobody Applications In Cancer Researchmentioning
confidence: 99%
“…In the preclinical setting, a CD40 bispecific γδ T-cell engager has shown to induce a powerful Vγ9Vδ2 T cell-dependent anti-leukemic response, also preventing CD40/CD40L-induced pro-survival signaling ( 68 ). More recently, a CD1d-specific Vγ9Vδ2-T cell engager based on single-domain antibodies has been explored in preclinical CLL models, showing its capability of determining cytokine production and degranulation by Vγ9Vδ2-T cells from both CLL patients and controls, and of inducing CD1d-dependent tumor lysis ( 69 ). Consistently with previous studies ( 70 ), the addition of ATRA increased CD1d expression and potentiated Vγ9Vδ2 T-cell engager-induced cytotoxicity of CLL cells ( 69 ).…”
Section: Successful Immunotherapy Options In Cllmentioning
confidence: 99%